1975
DOI: 10.1093/ajcp/63.4.493
|View full text |Cite
|
Sign up to set email alerts
|

Limits of Applicability of the Firefly Luminescence ATP Assay for the Detection of Bacteria in Clinical Specimens

Abstract: ATP measurement can be used as an indicator of biological mass, and the extreme sensitivity of the firefly ATP assay has led to its use in bacterial detection systems. Clinical specimens present problems not encountered with cultured isolates of known bacterial species. The lower limit of sensitivity for detecting bacteria using the firefly assay is 100,000 bacteria per ml. Non-bacterial ATP, which is probably present in all clinical specimens, produces false-positive results unless it is completely destroyed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Application of the luciferase enzyme and its substrate, luciferin, to the detection and quantitation of bacteria was originally described by Chappelle and Levin, who used a luminometer to measure bioluminescence (as relative light units [RLU]) (1). Initial attempts to apply this methodology to the enumeration of bacteria in clinical urine specimens were hampered by a number of problems not encountered when cultured isolates were quantified (4,12,16,25,26). These problems included the presence in urine of free nonbacterial ATP, the intracellular ATP contained in somatic cells, and luciferase inhibitory substances and the variation in ATP content among bacterial species, all of which compromised the quantitative aspect of the assay.…”
mentioning
confidence: 99%
“…Application of the luciferase enzyme and its substrate, luciferin, to the detection and quantitation of bacteria was originally described by Chappelle and Levin, who used a luminometer to measure bioluminescence (as relative light units [RLU]) (1). Initial attempts to apply this methodology to the enumeration of bacteria in clinical urine specimens were hampered by a number of problems not encountered when cultured isolates were quantified (4,12,16,25,26). These problems included the presence in urine of free nonbacterial ATP, the intracellular ATP contained in somatic cells, and luciferase inhibitory substances and the variation in ATP content among bacterial species, all of which compromised the quantitative aspect of the assay.…”
mentioning
confidence: 99%
“…A major problem with the measurement of microbial ATP is the large amounts of non-bacterial ATP found in somatic cells in specimens [21] . Effective removal of non-bacterial ATP before release of microbial ATP are crucial for the accurate determination of the target ATP.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical solution or physical extraction methods were used in liquid samples (Selan et al, 1992;Siro et al, 1982). Some false negative results were described in few studies (Conn et al, 1975;Kolbeck et al, 1985). Additional studies investigated the cause of false negative results and demonstrated that ATP extraction was not efficient.…”
Section: Atp-bioluminescence Applicationsmentioning
confidence: 99%